2012
DOI: 10.1111/j.1464-410x.2012.11398.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of low free to total PSA ratio in prostate cancer screening: detection rates, clinical and pathological findings in Brazilian men with serum PSA levels <4.0 ng/mL

Abstract: E 6 5 3What ' s known on the subject? and What does the study add? In spite of its low specifi city, PSA is the most widely used screening test for prostate cancer (PCa), and is considered the main cause of the stage migration recently observed. The ratio of free to total PSA (%fPSA) has been shown to increase PSA accuracy in cancer detection; however, few screening studies have systematically evaluated its role in cancer detection rates in men with PSA levels < 4.0 ng/mL and normal DRE.The present study suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
1
13
0
2
Order By: Relevance
“…All patients had clinical stage I and 96.8% had Gleason score ≤ 7. After radical prostatectomy, 82.4% had pathological stage T2 and 17.6% had pathological stage T3 (20). In our study we have found similar results regarding prostate biopsy predictive positive value.…”
Section: Discussionsupporting
confidence: 79%
“…All patients had clinical stage I and 96.8% had Gleason score ≤ 7. After radical prostatectomy, 82.4% had pathological stage T2 and 17.6% had pathological stage T3 (20). In our study we have found similar results regarding prostate biopsy predictive positive value.…”
Section: Discussionsupporting
confidence: 79%
“…Prevention programmes carried out by the Brazilian Government are mostly opportunistic and Hospital de Câncer de Barretos is one of the proponents institutions of prevention programs for skin cancer [11], cervix, prostate [12,13] and breast cancer [14] recognized in the country. The effectiveness of these programs is perceived through the large number of patients recruited from around the country that are sent to the institution for clinical and complementary examination and specialized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We performed an analysis on the database of the Mobile Cancer Prevention Units (MCPU) program (14), which visited 231 cities of six Brazilians states between 2004 and 2007, including 17.571 volunteers for PSA-based PCa screening, aged ≥45 years. There was no upper age cut-off on those willing to volunteer, as reported by Faria et al (14,17,18).…”
Section: Methodsmentioning
confidence: 99%
“…The criteria for prostate biopsy were: suspicious digital rectal examination (DRE) findings, or PSA >4.0ng/ml, or PSA 2.5-4.0ng/ml with free/total PSA ratio ≤15% (which was performed to assess the increase in the PCa detection rate in one preliminary study of the MCPU program, when the literature lacked data to the date) (18).…”
Section: Methodsmentioning
confidence: 99%